Decorin differentially modulates the activity of insulin receptor isoform A ligands - Morcavallo, Alaide (2014)
The proteoglycan decorin, a key component of the tumor stroma, regulates the action of several tyrosine-kinase receptors, including the EGFR, Met and the IGF-IR. Notably, the action of decorin in regulating the IGF-I system differs between normal and transformed cells. In normal cells, decorin binds with high affinity to both the natural ligand IGF-I and the IGF-I receptor (IGF-IR) and positively regulates IGF-IR activation and downstream signaling. In contrast, in transformed cells, decorin negatively regulates ligand-induced IGF-IR activation, downstream signaling and IGF-IR-dependent biological responses. Whether decorin may bind another member of the IGF-I system, the insulin receptor A isoform (IR-A) and its cognate ligands, insulin, IGF-II and proinsulin, has not been established. Here we show that decorin bound with high affinity insulin and IGF-II and, to a lesser extent, proinsulin and IR-A. We utilized as a cell model system mouse embryonic fibroblasts homozygous for a targeted disruption of the Igf1r gene (designated R(−) cells) which were stably transfected with a human construct harboring the IR-A isoform of the receptor. Using these R(−)/IR-A cells, we demonstrate that decorin did not affect ligand-induced phosphorylation of the IR-A but enhanced IR-A downregulation after prolonged IGF-II stimulation without affecting insulin and proinsulin-dependent effects on IR-A stability. In addition, decorin significantly inhibited IGF-II-mediated activation of the Akt pathways, without affecting insulin and proinsulin-dependent signaling. Notably, decorin significantly inhibited IGF-II-mediated cell proliferation of R(−)/IR-A cells but affected neither insulin- nor proinsulin-dependent mitogenesis. Collectively, these results suggest that decorin differentially regulates the action of IR-A ligands. Decorin preferentially inhibits IGF-II-mediated biological responses but does not affect insulin- or proinsulin-dependent signaling. Thus, decorin loss may contribute to tumor initiation and progression in malignant neoplasms which depend on an IGF-II/IR-A autocrine loop.